Coping With COVID-19 Pandemic: Role of Civil Society Organization in Nepal - Ghimire, Dipesh Kumar (Patan Pragya, 2022)
The World Health Organization (WHO) declared COVID-19 outbreak a pandemic on 11 March2020. The escalation of COVID-19 around the world has been adversely affecting the globe.COVID-19 has impacted almost all sectors in Nepal as well. The Government of Nepal (GoN) has-been taking various actions to respond to the health crisis created by COVID-19. The Go announced a lockdown and invited civil society organizations (CSOs) to support the government to COVID-19 response. Since inception CSOs have been playing a role of watchdog during the crisis in Nepal. They have been working in the frontline in providing essential services, documenting human right violation incidents, or advocating for policy change among others. The GoN has urged CSOs to divert funds and provide support to COVID-19 response. As a result, various humanitarian supports have been provided by CSOs to the needy people. This study has tried to analyze the good practices and interventions by CSOs during COVID-19 pandemic. The study finds out that the CSOs have been contributing to the society during the COVID-19 crisis in two ways. The first one is the direct support towards affected people and the second one is strengthening the Government institutions and mechanism to respond effectively. CSOs are also supported to improve the community engagement, promoting equality and governance and humanitarian support.